2015
DOI: 10.1016/j.juro.2015.05.081
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Spermatic Cord Denervation as a Treatment for Chronic Scrotal Content Pain: A Multicenter Open Label Trial

Abstract: After proper selection of patients microsurgical spermatic cord denervation seems to be a safe and efficient procedure to treat chronic scrotal content pain. Considering the limitations of the study, a randomized, controlled trial with longer followup is highly warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…Therefore, the treatment of chronic nonspecific CO is to remove or change the hyperactivated nerve pathways in the spermatic cord, so the targeted MDSC can be a successful option to treat CO. And our results show that targeted MDSC is effective in outcomes. However, numerous studies show variable success rates [1,9,10,23,24]. The PIQ-6 questionnaire showed that most patients had a significant pain relief after MDSC, and only 17.9% of patients continued to have postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the treatment of chronic nonspecific CO is to remove or change the hyperactivated nerve pathways in the spermatic cord, so the targeted MDSC can be a successful option to treat CO. And our results show that targeted MDSC is effective in outcomes. However, numerous studies show variable success rates [1,9,10,23,24]. The PIQ-6 questionnaire showed that most patients had a significant pain relief after MDSC, and only 17.9% of patients continued to have postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…In men with a history of previous inguinal hernia or vasectomy who present with a varicocele and pain, a spermatic cord block may be beneficial (18,19). Spermatic cord block with a long acting local anesthetic may aid in diagnosing neuropathic pain in addition to providing guidance as to the type of intervention that may be warranted.…”
Section: Presentation and Evaluationmentioning
confidence: 99%
“…Spermatic cord block with a long acting local anesthetic may aid in diagnosing neuropathic pain in addition to providing guidance as to the type of intervention that may be warranted. For example, if a patient has a greater than 50% reduction in pain after spermatic cord block, microsurgical cord denervation may be an effective treatment option (19,20). Men who report <50% resolution of symptoms after spermatic cord block may still benefit from varicocele repair, or they may have other mechanisms for pain such as unrecognized pathology, central sensitization, a coexisting pudendal pathway, or even malingering behavior (18).…”
Section: Presentation and Evaluationmentioning
confidence: 99%
“…They observed no intraoperative complications or testicular units loss but performed two reoperations for hematocele and hydrocele. Their study revealed that six months after surgery, 40 patients (80%) were pain-free, 6 (12%) had persistent pain and 4 (8%) had no change in pain (17). …”
Section: Treatmentmentioning
confidence: 99%